Volatile Composition, Antimicrobial Activity, and In Vitro Innate Immunomodulatory Activity of Echinacea purpurea (L.) Moench Essential Oils - Dosoky N. S. Noura; Kirpotina L. N. Liliya; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Khlebnikov A. I. Andrey Ivanovich; Lisonbee B. L. Brent; Black J. L. Jeffrey; Woolf H. Hillary; Thurgood T. T. Trever; Graf B. L. Brittany; Satyal P. Prabodh; Quinn M. T. Mark (2023, 2023)
Title screen